2011
DOI: 10.1155/2011/687834
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Planning Outreach Liaison Model in the Neighborhood Planning Process: A Case Study in Seattle′s Rainier Valley Neighborhood

Abstract: Our study examines a nontraditional engagement process employed by the City of Seattle during neighborhood plan updates. Adapting the trusted advocates model from the public health field, the city hired planning outreach liaisons (POLs) from 13 diverse community groups to solicit input from traditionally underrepresented residents. To explore the efficacy of this approach, we collected data through interviews with residents, neighborhood leaders, community development firm employees, university researchers, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The liaisons are indigenous to different groups, trusted and respected. Research has found that the “trusted advocates” model offers promise in improving transparency of local government intentions, facilitating communication of information, and coevolving solutions that fit needs of marginalized neighborhoods (Oshun, Ardoin, and Ryan 2011). To this end, use of the model throughout the scorecard application process could enhance prospects for producing information that is understood, trusted, and more likely to be used to coevolve equity policy solutions that build community resilience.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…The liaisons are indigenous to different groups, trusted and respected. Research has found that the “trusted advocates” model offers promise in improving transparency of local government intentions, facilitating communication of information, and coevolving solutions that fit needs of marginalized neighborhoods (Oshun, Ardoin, and Ryan 2011). To this end, use of the model throughout the scorecard application process could enhance prospects for producing information that is understood, trusted, and more likely to be used to coevolve equity policy solutions that build community resilience.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…The liaisons are indigenous to different groups, trusted and respected. Research has found that the "trusted advocates" model offers promise in improving transparency of local government intentions, facilitating communication of information, and coevolving solutions that fit the needs of marginalized neighborhoods (Oshun et al, 2011).…”
Section: Participatory Governancementioning
confidence: 99%
“…Inclusiveness is important, otherwise segments of society might be excluded; transparency is important to develop and maintain trust. This will involve avoiding approaches that allow dominant discourses to be imposed (Derkzen et al 2017),All ensuring democratic outcomes (Oshun et al 2011), and actively promoting inputs from less powerful neighbourhoods and residents (Lovell and Taylor 2013). Enhancing community understanding and participation will involve discussing BGI in clear and appealing ways (using local terminology rather than…”
Section: Engagement Process Principle (Epp)mentioning
confidence: 99%
“…Avoiding sophisticated techniques in which dominant discourses are imposed through participatory processes (i.e. being careful of elite capture) (Derkzen et al 2017, Raymond et al 2016 Ensuring democratic outcomes (Oshun et al 2011) Actively promoting inputs from less powerful stakeholders (neighbourhoods and residents) beyond those traditionally engaged (Lovell andTaylor 2013, O'Donnell et al 2017)…”
Section: Engagement Technique Dismantle Power Differentials and Ensur...mentioning
confidence: 99%